2019
DOI: 10.1002/jsid.824
|View full text |Cite
|
Sign up to set email alerts
|

Curved OLED microdisplays

Abstract: Technical background for CMOS substrate thinning of CEA‐LETI (historically developed for through silicon via technology as well as for more recent activity to provide curved image sensors, for IR as well as for visible spectra) has been applied to realize curved OLED‐based microdisplays. It will be shown that test OLEDs made onto silicon wafers as well as 873 × 500 WVGA, 0.38″ diagonal, and an innovative 1920 × 1200 WUXGA, 1″diagonal, CMOS‐based microdisplays can be curved at R = 45 mm radius of curvature (1D)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…However, the integration of OLEDs on silicon ICs renders it more difficult to obtain mechanically flexible devices even though extreme thinning of silicon allows to achieve a degree of mechanical flexibility. Integration of OLEDs on silicon is already used to make OLED microdisplays, [93,[263][264][265] some of which are bidirectional, e.g., to combine eye tracking and display function in optical viewfinders and smart glasses. [266] At the same time, this design flexibility of OLEDs represents challenges for the wider uptake of OLEDs in terms of system integration and manufacturing.…”
Section: Discussionmentioning
confidence: 99%
“…However, the integration of OLEDs on silicon ICs renders it more difficult to obtain mechanically flexible devices even though extreme thinning of silicon allows to achieve a degree of mechanical flexibility. Integration of OLEDs on silicon is already used to make OLED microdisplays, [93,[263][264][265] some of which are bidirectional, e.g., to combine eye tracking and display function in optical viewfinders and smart glasses. [266] At the same time, this design flexibility of OLEDs represents challenges for the wider uptake of OLEDs in terms of system integration and manufacturing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the horizontal FoV of the AR device was improved to 43°using a high-aspect-ratio (32:9) OLED microdisplay with a laterally expanded pin mirror array, as shown in Figure 8(a). Another approach to reducing the form factor of an AR device is by using a curved display, which makes the optical system simpler and lighter [52,53]. To fabricate the curved OLED microdisplay, the mechanical grinding process was used [52].…”
Section: High-performance Oled Microdisplays For Small-form-factor Ar Devicesmentioning
confidence: 99%
“…Another approach to reducing the form factor of an AR device is by using a curved display, which makes the optical system simpler and lighter [52,53]. To fabricate the curved OLED microdisplay, the mechanical grinding process was used [52]. After grinding, the thickness of the OLED microdisplay decreased to 70-130 μm, even as the electro-optical characteristics of the OLED were maintained.…”
Section: High-performance Oled Microdisplays For Small-form-factor Ar Devicesmentioning
confidence: 99%
“…Recently, it has been demonstrated that the approach used for the production of curved sensors [Lombardo(2019)] can be applied to create curved microdisplays thanks to the similarity between CMOS detectors and OLED (Organic Light-Emitting Diode) displays [Maindron(2019)]. This latest development opens new prospects for the creation of optical systems with curved focal surfaces.…”
Section: Introductionmentioning
confidence: 99%